IT Compliance and Controls: Best Practices for Implementation - DeLuccia, James J (Wiley, 2008)
IT Compliance and Controlsoffers a structured architectural approach, a 'blueprint in effect,' for new and seasoned executives and business professionals alike to understand the world of compliance?from the perspective of what the problems are, where they come from, and how to position your company to deal with them today and into the future.